2020
DOI: 10.1002/admi.201901876
|View full text |Cite
|
Sign up to set email alerts
|

Design of Sub‐Nanochannels between Graphene Oxide Sheets via Crown Ether Intercalation to Selectively Regulate Cation Permeation

Abstract: development and human activities, giving rise to the need for a method to obtain clean water resources. Membrane filtration, one of the processes to separate contaminants and salts from water, has attracted much attention as a way to secure clean water in an energy efficient manner. [2,3] As a result, various kinds of membrane materials, especially polymers, [4] have been widely studied for desalination and water purification. [5][6][7][8] However, the availability of polymer membranes in a large-scale process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Recently, graphene (GN) and graphene oxide (GO) membranes have aroused widespread attention owing to their excellent ion sieving performance. More importantly, researchers have found that more accurate ion sieving can be achieved by controlling the interlayer spacing of graphene-based membranes . Chen et al have achieved precise control of the interlayer spacing in GO membranes through noncovalent cation−π interactions between hydrate cations and the aromatic ring.…”
mentioning
confidence: 99%
“…Recently, graphene (GN) and graphene oxide (GO) membranes have aroused widespread attention owing to their excellent ion sieving performance. More importantly, researchers have found that more accurate ion sieving can be achieved by controlling the interlayer spacing of graphene-based membranes . Chen et al have achieved precise control of the interlayer spacing in GO membranes through noncovalent cation−π interactions between hydrate cations and the aromatic ring.…”
mentioning
confidence: 99%
“…The water permeance and ion rejection tests were conducted using a conventional dead-end filtration method. 7 The prepared GO membrane was placed on the bottom of the stirring cell, and the 50 mL of the salt solution was poured in the cell. The permeation test proceeded for 30 min under 1 bar of N 2 conditions, and the solution was agitated at 350 rpm in order to prevent the concentration polarization effect.…”
Section: Methodsmentioning
confidence: 99%
“…29 Especially for graphene, embedded crown ethers motifs have been studied by means of theoretical approximations and experimental observations, [30][31][32] whereas basal plane functionalized nanosheets with crown ethers have been evaluated for their cation permeation efficiency. 33 In the field of transition metal dichalcogenides, to the best of our knowledge, crown ethers have been only utilized as Li ions-containing intercalants within MoS2 exfoliated nanosheets serving as potential electrochemical switches. 34,35 The selective recognition of cations by tuning the size of the oxygencontaining macrocycles offers the advantage of developing responsive electrochemical platforms based on the host-guest interactions, arising from the stabilization of the cations within the macrocyclic polyether tether.…”
Section: Introductionmentioning
confidence: 99%